Planar Microwave Sensor with High Sensitivity for Material Characterization Based on Square Split Ring Resonator (SSRR) for Solid and Liquid - Maizatul Alice Meor Said; Zahriladha Zakaria; Mohamad Harris Misran; Mohd Azlishah bin Othman; Redzuan Abdul Manap; Abd Shukur bin Jaafar; Shadia Suhaimi; Nurmala Irdawaty Hassan (Politeknik Elektronika Negeri Surabaya (PENS), 2023)
Microwave resonator sensors are the most extensively used sensors in the food industries, quality assurance, medical, and manufacturing. Planar resonant technique is chosen as the medium for characterizing dielectric properties of material due to its compact in size, low cost and easy to fabricate. But these techniques have a low Q-factor and little sensitivity. This work uses the perturbation approach to overcome this technique's flaw, which is that Q-factor and resonant frequency are affected by the resonator's dielectric properties. This suggested sensor operated at 2.5GHz between 1GHz and 4GHz for material characterisation of solid and liquid samples. These sensors were constructed on a substrate made of RT/Duroid Roger 5880, which has a copper layer that is 0.0175 mm thick and has a dielectric constant of 2.2. This square split ring resonator (SSRR) sensor thus generates narrower resonant, low insertion loss, and a high Q-factor value of 430 at 2.5GHz. The SSRR sensor's sensitivity is 98.59%, which is higher than that of past studies. The application of the suggested sensor as a tool for material characterisation, particularly for identifying material attributes, is supported by this findings.